2018
DOI: 10.21873/anticanres.12247
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Laryngopharyngeal Reflux and Radiation-induced Mucositis in Head and Neck Cancer

Abstract: High RFS (i.e., increased likelihood of LPR) appears to be a potential risk factor for developing severe radiation-induced mucositis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…LPR has been demonstrated to be not only a potential factor for LCG development, but also an independent risk factor for severe radiation-induced mucositis in the prelaryngeal area. Previously, Eguchi et al ( 24 ) reported that patients with a high RFS, indicating high LPR likelihood before radiation, were more susceptible to radiation damage and developed severe laryngeal mucositis earlier than patients with low LPR likelihood. When PPI therapy was administrated, the mucositis was quickly ameliorated ( 25 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…LPR has been demonstrated to be not only a potential factor for LCG development, but also an independent risk factor for severe radiation-induced mucositis in the prelaryngeal area. Previously, Eguchi et al ( 24 ) reported that patients with a high RFS, indicating high LPR likelihood before radiation, were more susceptible to radiation damage and developed severe laryngeal mucositis earlier than patients with low LPR likelihood. When PPI therapy was administrated, the mucositis was quickly ameliorated ( 25 ).…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, we believe that under chronic stress of LPR, the laryngeal mucosa may be vulnerable to irradiation damage and may well facilitate radiation-related LCG formation after radiation. Following Eguchi et al ’s study ( 24 ), we used the RFS for LPR assessment before radiotherapy in our series. Unexpectedly, LCG tended to develop sooner post radiation in the high LPR likelihood group than in the low LPR likelihood group but had a longer remission time.…”
Section: Discussionmentioning
confidence: 99%
“…Pyrosis can also contribute to the development of stomatitis; in fact, it represents an inflammatory alteration to the mucosa of the upper gastrointestinal (GI) tract, most frequently occurring as a consequence of excessive acid reflux from the stomach to the esophagus or even the laryngopharynx [35]. Some preliminary studies have identified possible associations between chronic gastro-esophageal or laryngeal reflux disease and an increased onset of H&N cancers, particularly within the larynx [36]. Moreover, a higher severity of reflux disease has been described as a potential, significant risk factor for more serious radiation-induced mucositis in patients with stage I-II laryngeal and hypopharyngeal cancers [36].…”
Section: Stomatitismentioning
confidence: 99%
“…Some preliminary studies have identified possible associations between chronic gastro-esophageal or laryngeal reflux disease and an increased onset of H&N cancers, particularly within the larynx [36]. Moreover, a higher severity of reflux disease has been described as a potential, significant risk factor for more serious radiation-induced mucositis in patients with stage I-II laryngeal and hypopharyngeal cancers [36].…”
Section: Stomatitismentioning
confidence: 99%